The Watson Family, the Association for the Discountenancing of Vice and the Irish Cheap Repository Tracts. (16th September 2020) - Stoker, David
Abstract: Although the history of Hannah More's Cheap Repository Tracts in England and America is well known, little has been written about the 270 or more editions published in Ireland 1795- c . 1830. They were first published by William Watson, a Dublin bookseller who, in 1792, had founded The Association for the Discountenancing of Vice (ADV). This article describes the founding and growth of the Association and the involvement of Watson and his son in the publishing of the tracts during the late 1790s. It also describes the role of the Watson family, the ADV and the Cheap Repository tracts during the Anglican Evangelical Crusade (1801–1830) after the 1798 rebellion in Ireland. Whilst many members of the Dublin book trade suffered from a severe economic depression after 1801, the Watson family continued to prosper, thanks to the printing and publishing work undertaken on behalf of the ADV. The Watson family business closed in 1832, but the ADV has lasted to the present day operating under a different name.